AP5Z1/SPG48 frequency in autosomal recessive and sporadic spastic paraplegia. Issue 5 (25th May 2014) - Schlipf, Nina A.; Schüle, Rebecca; Klimpe, Sven; Karle, Kathrin N.; Synofzik, Matthis; Wolf, Julia; Riess, Olaf; Schöls, Ludger; Bauer, Peter
Abstract Hereditary spastic paraplegias (HSP) constitute a rare and highly heterogeneous group of neurodegenerative disorders, defined clinically by progressive lower limb spasticity and pyramidal weakness. Autosomal recessive HSP as well as sporadic cases present a significant diagnostic challenge. Mutations in AP5Z1, a gene playing a role in intracellular membrane trafficking, have been recently reported to be associated with spastic paraplegia type 48 (SPG48). Our objective was to determine the relative frequency and clinical relevance of AP5Z1 mutations in a large cohort of 127 HSP patients. We applied a targeted next‐generation sequencing approach to analyze all coding exons of the AP5Z1 gene. With the output of high‐quality reads and a mean coverage of 51‐fold, we demonstrated a robust detection of variants. One 43‐year‐old female with sporadic complicated paraplegia showed two heterozygous nonsynonymous variants of unknown significance (VUS3; p.[R292W];[(T756I)]). Thus, AP5Z1 gene mutations are rare, at least in Europeans. Due to its low frequency, systematic genetic testing for AP5Z1 mutations is not recommended until larger studies are performed to add further evidence. Our findings demonstrate that amplicon‐based deep sequencing is technically feasible and allows a compact molecular characterization of multiple HSP patients with high accuracy.